La configuración ideológica del insularismo en el Regionalismo español: El caso de La barraca de Blasco Ibáñez - Minardi, Adriana Elizabeth (2015)
This paper aims to study the ideological configurations that arise from the effect of insularity in "La barraca" (belonging to the regionalist novel cycle) by the Spanish writer, Vicente Blasco Ibáñez. One of the main assumptions of this article is that the island effect is a narrative device which suggests regionalism as a class contradiction but also as a form of resistance against urban culture. The author of this article recognizes three rhetorical strategies employed by Blasco Ibáñez: mythemes dislocation, analysis of the effect of the Hegelian master / slave relationship, and the dialectic established between totem and taboo. In conclusion, the author focuses on the concept of politically peripheral nationalism.